Infant Health, Cognitive Performance and Earnings: Evidence from Inception of the Welfare State in Sweden - Martin Karlsson; Nina Schwarz; Sonia Bhalotra; Therese Nilsson (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We estimate impacts of exposure to an infant health intervention trialled in Sweden in the early 1930s using purposively digitised birth registers linked to school catalogues, census files and tax records to generate longitudinal data that track individuals through four stages of the life-course, from birth to age 71. This allows us to measure impacts on childhood health and cognitive skills at ages 7 and 10, educational choice during young adulthood, employment, earnings and occupation at age 3640, and pension income at age 71. Leveraging quasi-random variation in eligibility by birth date and birth parish, we estimate that an additional year of exposure was associated with substantial increases in earnings and (public sector) employment among women, alongside no improvements for men. Earnings gains for women were concentrated in the top quintile of the distribution. The earnings results appear to be related to the intervention having made it more likely that primary school test scores for girls were in the top quintile of the distribution and, related, that they attended secondary school. The greater investments of women in education are consistent with their comparative advantage in cognitive tasks, but opportunities are also likely to have played a role. Our sample cohorts were exposed to a massive expansion of the Swedish welfare state, which created unprecedented employment opportunities for women.
Keywords: I15; I18; H41; 330; Infant health; early life interventions; cognitive skills; education; earnings; occupational choice; programme evaluation; Sweden